The newly applied mortars in mosaic restoration - Fabiana Moro; Angelica Pujia (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The restoration of the Dionysos mosaic in Cologne gave us the opportunity for analysing the process involved in the choice of interstitial mortars in mosaics that were detached from their original site and re-layed on new supports, thus losing their original setting bed. This intervention lead us to investigate the relationships between restoration and a philological perspective and the damages following the stripping of mosaics.